Perilaku Politik Elit Struktural Muhammadiyah Dalam Pemilihan Calon Anggota DPD RI Periode 2019-2024 Di Kabupaten Pangkep - Amin, M; Bonto, Saifullah; Khaerah, Nur (Kybernology : Journal of Government Studies, 2021)
The purpose of this study is to find out the form of political behavior of Muhammadiyah structural elites in the selection of DPD RI members. This research method is a qualitative method that provides an objective picture of the actual state of the object being studied and the type of research used is the phenomenological type. The data used is the primary data source and secondary data source with the number of informants as many as 7 people. And documentation. Data analysis techniques used in this study are data reduction, data presentation, and conclusion withdrawal. The data usage used is source triangulation, triangulation technique and time triangulation. This research aims to find out position analysis, reputation analysis and analysis of decisions of Muhammadiyah structural elite Pangkep’s regency. The results showed that the pattern of political behavior of Muhammadiyah structural elites in Pangkep Regency tends to be moderate-accommodating by being characterized by the participation of Muhammadiyah structural elites of Pangkep Regency in elections by choosing certain DPD RI Member Candidates without excessive fanaticism, then there is a willingness to cooperate and establish adaptive and rational relationships with prospective DPD RI Members without having to fuse themselves